Factors affecting the use of uniride bicycle-sharing in a University setting - Abdul Azeez Kadar Hamsa, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Bicycle-sharing has become one of the most popular transportation modes especially for short-distance travel and supports sustainable transportation. This concept is relatively new in Malaysia and cycling culture is not widely spread among the community. This has provided growing difficulties and challenges to the use of bicycle-sharing service especially in the university campuses. The increasing use of motorized vehicles and decreasing use of bicycles has not only affected bicycle-sharing services but also the environment of the campus. Thus, the aim of this study is to identify the significant factors affecting the use of UniRide bicycle-sharing and the existing level of use of bicycle-sharing in International Islamic University Malaysia (IIUM), Gombak Campus. The data required for this study were collected by using an online questionnaire survey targeting the students who live on-campus. The collected data were analysed by using both univariate and bivariate analysis methods. The results of the analysis show that most of the respondents felt that convenience and bicycle infrastructure are the main factors that affect the use of UniRide bicycle-sharing in IIUM. Most of the respondents also stated that riding bicycles on a dedicated and exclusive bicycle lane would enhance the safety of the bicycle users. Few recommendations to improve the existing UniRide bicycle-sharing service on-campus were formulated..